1994
DOI: 10.1073/pnas.91.18.8373
|View full text |Cite
|
Sign up to set email alerts
|

Design of a "minimAl" homeodomain: the N-terminal arm modulates DNA binding affinity and stabilizes homeodomain structure.

Abstract: This report investigates the sequence specificity requirements for homeodomain structure and DNA binding activity by the design and synthesis of a "minimAl" homeodomain (for mimalist design and alanine sning mutagenesis) which contain the consensus residues and in which all nonconsensus residues have been replaced with alanin. The murine homeodomain Msx served as the prototype for the minimAl homeodomain, Ala-Msx. We show that Ala-Msx binds to DNA specifically, albeit with lower affinity than Msn. A derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…4D). This finding was not surprising since many of the alanine-substituted residues mediate DNA-protein contact (e.g., Msx-A and Msx-E) or stabilize the DNA-protein interaction (e.g., Msx-B) (23). However, it is noteworthy that some of the mutants that abolished DNA binding activity did not abolish repression or TBP interaction (Fig.…”
Section: Methodsmentioning
confidence: 88%
“…4D). This finding was not surprising since many of the alanine-substituted residues mediate DNA-protein contact (e.g., Msx-A and Msx-E) or stabilize the DNA-protein interaction (e.g., Msx-B) (23). However, it is noteworthy that some of the mutants that abolished DNA binding activity did not abolish repression or TBP interaction (Fig.…”
Section: Methodsmentioning
confidence: 88%
“…There has been ample speculation that the homeodomain also mediates protein-protein interactions, and several functional associations have been described (66,88,90). The contribution of the homeodomain as a structural motif has been less well explored, although we have observed that mutations within the homeodomain of Msx-1 affect both structure and stability (14,78).…”
Section: Discussionmentioning
confidence: 98%
“…Since our data show that homeodomain DNA-binding sites are not required for repression, it is likely that the Msx-1 homeodomain serves an alternative function. For instance, it may mediate interactions with other protein factors (22,66,88,90), or it may provide a scaffold which maintains appropriate tertiary structure of Msx-1 (78). DNAbinding domains have been shown to serve various functions in transcriptional regulation, particularly as surfaces for proteinprotein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The conserved regions among the MSX proteins are the MSX homology regions I, II and III (MHR1 to -III), the extended homeodomain (EHD), and the homeodomain (Davidson 1995). The homeodomain consisting of 60 amino acids numbered 166-225 is subdivided into the N-terminal arm (NT arm) and helices I, II and III, which contribute to protein stability, DNA binding specificity, transcriptional repression and protein interactions (Shang et al 1994;Isaac et al 1995;Zhang et al 1996Zhang et al , 1997. In the MSX1 homeodomain, there are several conserved residues that constitute a consensus sequence, which promotes tertiary structure and mediates DNA binding activity (Scott et al 1989;Laughon 1991;Billeter 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In the MSX1 homeodomain, there are several conserved residues that constitute a consensus sequence, which promotes tertiary structure and mediates DNA binding activity (Scott et al 1989;Laughon 1991;Billeter 1993). Consensus residues in helices I-III furnish the hydrophobic core and preserve the amphipathic nature of the alpha helices, whereas other consensus residues in helix III and in the N-terminal arm contact DNA (Shang et al 1994).…”
Section: Discussionmentioning
confidence: 99%